Advantages of adapted goat milk-based formulas for functional disorders of the gastrointestinal tract in young children with artificial feeding - N. A. Geppe; A. V. Meleshkina; E. A. Yablokova; S. N. Chebysheva (Лечащий Врач)
Breast milk is the standard for feeding infants in their first year of life. However, in the Russian Federation, less than half of children under 3 months of age receive breastfeeding, which makes it relevant to choose an adapted mixture for both parents and pediatricians. The composition and characteristics of goat milk allow us to recommend adapted infant formula based on it for the successful artificial feeding of infants. The article presents data on the safety and good tolerance of goat milk-based formulas, and the positive effect of these formulas on digestion in children up to a year is emphasized.